Lack of Associations Between Dietary Intake and Gastrointestinal Symptoms in Autism Spectrum Disorder - Ferguson, Bradley J.; Dovgan, Kristen; Severns, Danielle; Martin, Shannon; Marler, Sarah; Gross Margolis, Kara; Bauman, Margaret L.; Veenstra-VanderWeele, Jeremy; Sohl, Kristin; Beversdorf, David Q. (Frontiers in Psychiatry, 2019)
Background: Many individuals with autism spectrum disorder (ASD) have significant gastrointestinal (GI) symptoms, but their etiology is currently unknown. Our prior work showed that GI symptoms correlated with stress reactivity, but the question remained as to the potential role of variations in diet in this relationship. Many families modify the diet of children with ASD, including diets with increased omega-3 fatty acids or diets free of gluten and/or casein, which may also impact GI symptoms and nutrition. However, little is known about the relationship between nutritional intake and GI symptomatology in ASD. The objective of this study was to assess the relationships between GI symptoms, omega-3 intake, micronutrients, and macronutrients in children with ASD. Methods: A total of 120 children diagnosed with ASD participated in this multisite study. A food frequency questionnaire was completed by the patient’s caretaker. The USDA Food Composition Database was utilized to provide nutritional data for the food items consumed by each participant. GI symptomatology was assessed using a validated questionnaire on pediatric gastrointestinal symptoms. Results: There were no significant associations between GI symptoms and the amount of omega-3 fatty acids and/or other micro and macro nutrients contained in the diet. Conclusions: This study suggests that dietary variations do not appear to drive GI symptoms, nor do GI symptoms drive dietary variations in those with ASD; although causation cannot be determined with this observational assessment. Further, there may be other factors associated with lower GI tract symptoms in ASD, such as increased stress response.